Exploration of Domestic and Foreign Tourist Preferences toward Newa Concept-Based Tourism Activities in Bali - I Gusti Made Sukaarnawa; Darsana, I Made; Paramitha, Made Widya (Brilliant International Journal Of Management And Tourism, 2025)
Research purposes This study aims to identify tourist preferences for four types of tourism activities classified under the NEWA concept: Nature , Ecotourism , Wellness , and Adventure . It also reveals how tourists prioritize these activities during their visits, thus providing in-depth insights into what tourists are most interested in. The expected benefit is to assist tourism village managers, policy makers, and tourism industry players in designing and developing tourism products and services that are more in line with market preferences. The type of research is descriptive quantitative with a survey data collection method using a questionnaire instrument. Respondents numbered 200 people who were domestic and international tourists visiting tourist attractions in Bali, including Kuta Beach, Ubud, Tanah Lot, and Kintamani. The data analysis technique used was descriptive statistical analysis. The results found that the majority of tourists showed a strong interest in tourism villages, especially those based on the NEWA concept. This indicates a great potential for the development of tourism villages that prioritize elements of nature, sustainability, and health, which is in line with the global trend of tourism that is increasingly concerned with the environment and well-being. Nature -based activities ranked highest in terms of tourist interest, followed by Adventure, Wellness , and Eco- friendly NEWA activities . This reflects that tourists tend to be more interested in experiences that involve direct interaction with nature, whether through environmental exploration, adventure, or activities that support health and well-being in the outdoors